Immunohistochemical Classification of Ampullary Carcinomas: Critical Reappraisal Fails to Confirm Prognostic Relevance for Recently Proposed Panels, and Highlights MUC5AC as a Strong Prognosticator. (July 2017) - Xue, Yue; Reid, Michelle D.; Balci, Serdar; Quigley, Brian; Muraki, Takashi; Memis, Bahar; Xia, Jun; Hacihasanoglu, Ezgi; Bedolla, Gabriela; Pehlivanoglu, Burcin; Kim, Grace E.; Tajiri, Takuma; et al.
Abstract : Recently, immunohistochemistry-based classifications of ampullary carcinomas have been proposed (Ang and colleagues [PMID: 24832159]; Chang and colleagues [PMID: 23439753]). In this study, the prognostic value of Ang/Chang panel markers (CK20, MUC1, MUC2, CDX2) as well as other markers (CK7, MUC5AC, and MUC6) were tested on full-faced sections of 136 ampullary carcinoma resections with substantial (>5 mm) invasion. Immunohistochemistry was correlated with both histologic classification (intestinal [INT], pancreatobiliary [PB], or nontubular based on ≥3/5 observer agreement) and clinical outcome. No prognostic correlation was found with MUC1, CDX2, MUC2 or CK20 despite testing with different quantitative cutoffs. CK7 and CK20 were nonspecific. Ang classification had reasonable correlation with histologic subclassification of tubular cases as INT versus PB with high specificity but low sensitivity and ambiguous category was large (29%) and included also some classical cases. Prognostically, Ang classification approached but did not reach statistical significance, even when their large "ambiguous" group was eliminated and only tubular cases were analyzed (Ang-INT vs. Ang-PB; P =0.08). The Chang panel, in which the definition of the INT subcategory is not clearly defined, only marginally reached prognostic significance when tested as MUC1+/CDX2− versus MUC1−/CDX2+ and only by Wilcoxon test ( P =0.0485) but 31% of the cases were "unclassifiable." The only individual marker that was found to have direct and strong correlation with the clinical outcome was MUC5AC (not used in the Ang or Chang panels), with statistically significant survival differences found with various cutoffs tested (for 20% cutoff, 5-y survival, 68% vs. 31%; P =0.0002). In addition, MUC5AC significantly stratified the histologically PB and INT cases ( P =0.01 and 0.03, respectively), as well as Ang's ambiguous and Chang's unclassified cases ( P =0.006 and 0.007, respectively). In conclusion, the widely used putative lineage markers, MUC1/MUC2/CK7/CK20/CDX2, do not seem to have direct/significant prognostic correlation either individually or in combination of Ang and Chang panels. Ang panel is helpful as an adjunct in determining the cell lineage with a few caveats. MUC5AC proves to be a significant independent prognosticator and should be incorporated into evaluation of ampullary carcinomas.